2016
DOI: 10.5032/jae.2016.01012
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Pre-service Agricultural Science Teachers’ Interest and Participation in International Experiences: Motivations and Barriers

Abstract: The importance of creating global mindedness within pre-service agricultural science teachers through international experiences cannot be overstated. However, providing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Unfortunately, preservice agriculture teachers prefer a global experience in a country similarly developed to the United States and with a large group of their peers (Murphrey, Lane, Harlin, & Cherry, 2016) limiting the opportunity for exposure that assist in the expansion of, not only their cultural perspective, but also the global mindset and cultural understanding of their students (Banks, 2014). However, once enrolled in the courses of preference, students report to not be fully engaged (Bunch, Lamm, Israel, & Edwards, 2013).…”
Section: Need For the Studymentioning
confidence: 99%
“…Unfortunately, preservice agriculture teachers prefer a global experience in a country similarly developed to the United States and with a large group of their peers (Murphrey, Lane, Harlin, & Cherry, 2016) limiting the opportunity for exposure that assist in the expansion of, not only their cultural perspective, but also the global mindset and cultural understanding of their students (Banks, 2014). However, once enrolled in the courses of preference, students report to not be fully engaged (Bunch, Lamm, Israel, & Edwards, 2013).…”
Section: Need For the Studymentioning
confidence: 99%
“…In order for these benefits to be felt by students, faculty, and communities, they must first commit to an international experience. (Briers, Shinn, & Nguyen, 2010;Bunch, Cater, & Rampold, 2017;Bunch, Lamm, Israel, & Edwards, 2013;Murphrey, Lane, Harlin, & Cherry, 2016). Motivations for undergraduate students to study abroad include enhancing overall life experiences, opportunity to experience other cultures, and increased employability potential (Briers et al, 2010).…”
Section: Study Abroad Experiencesmentioning
confidence: 99%
“…Students are also strongly motivated by the design of the study abroad program. For example, in a mixed-methods sequential explanatory study, by Murphrey et al (2016), findings indicate that undergraduate pre-service agricultural educators preferred to study in developed countries in programs that last between one and six weeks. This is corroborated with similar findings by Parr, Peake, and Riley (2013) and Briers et al (2010).…”
Section: Study Abroad Experiencesmentioning
confidence: 99%
“…The theory of planned behavior was selected as it "provides a useful conceptual framework for dealing with the complexities of human social behavior" (Ajzen, 1991, p. 206). Furthermore, this theory provides a means of understanding individuals' decisions to act and can allow for the development of programs to meet targeted academic needs (Murphrey, Lane, Harlin, & Cherry, 2016). Ajzen and Fishbein (2005) suggested that an individual's behavior is a result of the combination of beliefs, attitudes, and intentions.…”
Section: Introduction and Theoretical Frameworkmentioning
confidence: 99%